PARTISIPASI MASYARAKAT LOKAL DI DAYA TARIK WISATA HUTAN PINUS DI KABUPATEN GORONTALO - Srilian Laxmiwaty Dai; Irma K. Hatibie (Tulisan Ilmiah Pariwisata (TULIP), 2020)
The Objectives of this research are to figure out the local community involvement in the management and the development of Hutan Pinus Dulamayo Tourist Attraction and to know how to improve the local community involvement. The method of this research is qualitative metode with observation, interview and documentation. The result of this research was the lack of local community involvement in the management and the development of Hutan Pinus Dulamayo Tourist Attraction. The management of this tourist attraction is handled by only some people wich did not give a big multiflier effect to all of the local community in Dulamayo Village.